2012
DOI: 10.1617/s11527-012-9994-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and humidity influences on the on-site active marine corrosion of reinforced concrete elements

Abstract: Reinforcement corrosion is a main durability issue for reinforced concrete structures in the marine environment. Environmental actions on the corrosion rate have been documented by several researchers on actively corroding reinforced concrete structures. Therefore, considering the influences of ambient temperature and relative humidity is very important for prospective studies of corroding structures. In this paper, active corrosion of concrete members in the marine environment was observed for 4.8 years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…As both parameters can strongly vary, even over a single day, a measurement procedure must be defined for the accurate extrapolation of instantaneous measurements to annual corrosion rates and to incorporate the RH and T changes into service life models [448][449][450]. One solution is to carry out several measurements at specific times with very different conditions, at least four-times a year, to study the seasonal cycle for calculating an average value.…”
Section: Limitation On the Evaluation Of Corrosion Rate And Interest Of Combining Ndt Methodsmentioning
confidence: 99%
“…As both parameters can strongly vary, even over a single day, a measurement procedure must be defined for the accurate extrapolation of instantaneous measurements to annual corrosion rates and to incorporate the RH and T changes into service life models [448][449][450]. One solution is to carry out several measurements at specific times with very different conditions, at least four-times a year, to study the seasonal cycle for calculating an average value.…”
Section: Limitation On the Evaluation Of Corrosion Rate And Interest Of Combining Ndt Methodsmentioning
confidence: 99%
“…Several researchers have concluded that the chloride ion erosion rate increases with temperature when the environmental temperature is below 40 degrees Celsius [27][28][29].…”
Section: Marine Environmental Chamber Control Parametersmentioning
confidence: 99%
“…(3) Relative humidity has a decisive influence on the degree of exposure to the sea atmosphere. Zaccardi et al [24] have studied the influence of ambient temperature and relative humidity in the corrosion of reinforcing bars in RC structures in a marine environment. Bouteiller et al [25] demonstrated that temperature and humidity interact with each other in the corrosion processes.…”
Section: Influence Of the Marine Atmosphere On Rc Building Structuresmentioning
confidence: 99%